Challenges in teaching ELF in the periphery: the Greek context - Sifakis, N. (ELT Journal, 2009)
The paper presents a notional account of the challenges facing the introduction of English as an international lingua franca (ELF) curriculum in the state schools of the expanding circle, taking Greece as a case in point. It broadly delineates an ELF curriculum as one focusing on the skills necessary for carrying out successful communication involving non-native speakers and then highlights a set of challenges linked to both teaching context and teachers’ perceptions of professional identity. It focuses on challenges related to three facets of the professional identity of academically trained Greek state school EFL teachers, namely, their roles as users, specialists, and, ultimately, custodians of English for their learners and wider community. These facets are discussed with reference to a description of the country's current sociolinguistic and educational profile. The paper concludes with an overview of the strengths of an ELF curriculum for Greek state schools and discusses implications for ELF teacher education.